To stent or not to stent: the use of transanastomotic biliary stents in liver transplantation and patient outcomes. Issue 6 (17th April 2018) - Ong, Michelle; Slater, Kellee; Hodgkinson, Peter; Dunn, Nathan; Fawcett, Jonathan
Abstract : Background: There is no substantial evidence for the use of biliary stents in bile duct reconstruction during liver transplantation. Method: A longitudinal, retrospective cohort study was performed to compare biliary complications between stented and non‐stented patients between 2011 and 2015 at the Princess Alexandra Hospital, Brisbane, Australia. Results: We found no significant difference in biliary complications between stented and non‐stented groups. Stented patients were 3.31 times as likely to require subsequent intervention, mainly in the form of stent removal. Conclusion: These results suggest that there is limited benefit in the placement of endobiliary stents in liver transplantation. Given that this was purely an observational study, causality cannot be proven and a prospective cohort trial would be beneficial in further defining these relationships.